(untitled) (Anclajes, 2026)
The use of iconoclasm as a tool of creative destruction continues to be remarkably fertile within the contemporary human artistic field. In order to account for this, a brief overview is offered of the drifts it has adopted since its promulgation as an edict. Later, taking as a reference the works of the visual artists Rogelio López Cuenca and David Bestué, a possible typology of the iconoclastic procedure is proposed, which is broken down into ‘gestural’ and ‘material’. The aim, ultimately, is to certify the different ways in which both Bestué and López Cuenca make use of iconoclastic language to intervene in the symbolic order that governs our cities.